A Parental Behavior Scale in Pediatric Dentistry: The Development of an Observational Scale - Tania Vanhée; Farah Dadoun; Astrid Vanden Abbeele; Peter Bottenberg; Wolfgang Jacquet; Isabelle Loeb (MDPI AG, 2023)
Children's treatment means a triangular relationship between the child, practitioner, and parent, with specific interactions influencing the procedure. The objective was to create and validate a hetero-rating scale of parental behavior and verify the correlation between child and parental behavior during pediatric dentistry sessions. Treatment sessions were recorded and evaluated, including 60 children representing three age groups. Two raters interpreted the resulting video clips using the modified Venham scale for children and the new hetero-rating scale for parents. They analyzed the videos twice and attributed scores at different time points of the appointment. The correlation between parental behavior upon entrance and the children's behavioral at the dental office in the treatment stage was significantly positive in both raters (Kendall Tau: 0.20-0.30). Furthermore, a panel of 20 dental practitioners scored a randomized selection of five recordings per age group. The level of agreement between the two experts was higher than that between the 20 clinicians. Venham types of scale involving multiple aspects can be used in research, but their application in dental practice requires further development. The link between parental anxiety and child anxiety is confirmed, but further research is required to incorporate specific aspects of treatment and parental behavior.